2012
DOI: 10.3133/sir20125244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two regression-based approaches for determining nutrient and sediment fluxes and trends in the Chesapeake Bay watershed

Abstract: Graphs showing the observed concentration versus discharge relation, observed and ESTIMATOR-predicted concentration versus discharge relation, residual (observed minus predicted) plot for ESTIMATOR predictions, observed and WRTDS-predicted concentration versus discharge relation, and residual (observed minus predicted) plot for WRTDS predictions-3. Nitrate at Patuxent River near Bowie, Maryland (USGS Station 01594440

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 9 publications
(16 reference statements)
2
73
0
Order By: Relevance
“…And although our case study data set does not contain any censored values-i.e., concentrations reported as less than detection limit (typically 0.5 mg/L for SS)-there are published approaches for handling such data [e.g., Tobin, 1958], and others have shown how WRTDS can be implemented in such cases [Chanat et al, 2016;Moyer et al, 2012;Zhang et al, 2015]. In fact, WRTDS has already been adopted by many investigators to estimate concentration and flux for a variety of constituents, including nitrogen, phosphorus, chloride, and dissolved organic carbon.…”
Section: Methods Application: Case Study and Broader Relevancementioning
confidence: 99%
“…And although our case study data set does not contain any censored values-i.e., concentrations reported as less than detection limit (typically 0.5 mg/L for SS)-there are published approaches for handling such data [e.g., Tobin, 1958], and others have shown how WRTDS can be implemented in such cases [Chanat et al, 2016;Moyer et al, 2012;Zhang et al, 2015]. In fact, WRTDS has already been adopted by many investigators to estimate concentration and flux for a variety of constituents, including nitrogen, phosphorus, chloride, and dissolved organic carbon.…”
Section: Methods Application: Case Study and Broader Relevancementioning
confidence: 99%
“…We used the flux bias statistic here as a dimensionless representation of the difference between the sum of the estimated fluxes on all sampled days and the sum of the true fluxes on all sampled days. Overall, WRTDS is substantially less susceptible to serious flux bias; however, it is not immune to the problem (Moyer et al 2012;Hirsch 2014). Because WBT only works with FNF and FNC series, trend identifications of the non-normalized and flow series were examined using BFAST (Table 2).…”
Section: Wrtds Bootstrap Test (Wbt)mentioning
confidence: 99%
“…Accessed November, 2015, http://cbrim.er.usgs.gov/). A comparison to an alternative regression‐based model for evaluating nutrient flux, ESTIMATOR, suggested that WRTDS can produce more accurate trend estimates (Moyer et al ., ). As opposed to WRTDS, GAMs were initially developed in a more general context as a modification to generalized linear models to model a response variable as the sum of smoothing functions of different predictors (Hastie and Tibshirani, ; Wood, ).…”
Section: Introductionmentioning
confidence: 99%